General Outlines of the Modern Educational Development in the Countries of the European Union - Kučinskienė, Ramute (Acta Paedagogica Vilnensia, 2000)
Contemporary common characteristics of education in European Union countries were studied in the article. Main topics such as educational objectives, curriculum, teacher training and work in class were studied. Also ways of psychological, emotional, educational and vocational assistance for pupils in these countries were under review. Some important comparisons accordingly to Lithuania education could be done but it requires a special investigation.